Assessment of Physico-Chemical Parameters of River Water of Subarnarekha Basin In and Around Jharkhand Area. - Dr S.P.Rout ,Dr.Baidhar Sahu, Nirmal Kumar Bhuyan Dr. Nibedita Pattnayak (International Journal of Scientific Research and Management (IJSRM), 2017)
The present investigation is aimed at assessing the current physico-chemical characteristics along the Subarnarekha river in Jhadkhand and Odisha.Eight samples were collected along the stretches of Subarnarekha basin during the period (Water Year) June-2012 to May-2013 on the first working day of every month.Various physico-chemical parameters like pH, TDS, ,EC,DO,BOD,TotalHardness,Totalalkalinity,sodium,potassium,calcium,magnesium etc. were analysed. The study reveals that most of the parameters were found within permissible limits recommended by WHO and Indian Council of Medical Research (ICMR).